Основоположні принципи соціальної держави - Стеценко, С.Г. (Альманах права, 2012)
У статті висвітлюються проблемні питання основоположних принципів соціальної держави. Основну увагу приділено принципам рівності та справедливості. В статье освещаются проблемные вопросы основополагающих принципов социального государства. Основное внимание уделено принципам равенства и справедливости. Тhis article highlights the problematic issues of fundamental principles of the welfare state. Emphasis is placed on principles of equality and justice. In particular, it highlights the problem of the relations of equality and freedom. The principle of justice allows the presence of unequal initial human capabilities to provide a minimum adequate standard of living. The principle of justice allows the presence of unequal initial human capabilities to provide a minimum adequate standard of living. It is concluded that the principles of equality and justice have become a kind of «roadmap» for the state social policy and at the same time «barrier» of hasty, unfounded, politically conditioned efforts of the state in the social sphere.